2010
DOI: 10.1111/j.1754-7121.2010.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

The leadership role of the municipal chief administrative officer

Abstract: A great deal has been written about leadership, but not much of it focuses on the unique role of the municipal chief administrative officer (CAO). This article argues that the complexity of the position of municipal CAO comes about because the incumbent must lead in three different directions simultaneously: down (dealing with subordinates), out (dealing with residents' groups, media, and other governments), and up (dealing with the mayor and council). Leading in each of those directions requires a different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…Studying the transformation in the local level interaction reveals a trend where the traditional roles of the dualistic local level leaders intermingle. This is in line with the idea of the political bureaucrat presented by Siegel (2010). It is required that politicians have more and more substance knowledge while the municipal CEO is changing from a task-oriented manager, or a classical bureaucrat, to a relationship-oriented leader or political bureaucrat.…”
Section: Explosion Of Interaction Needs and Emergence Of Instant Intesupporting
confidence: 58%
See 2 more Smart Citations
“…Studying the transformation in the local level interaction reveals a trend where the traditional roles of the dualistic local level leaders intermingle. This is in line with the idea of the political bureaucrat presented by Siegel (2010). It is required that politicians have more and more substance knowledge while the municipal CEO is changing from a task-oriented manager, or a classical bureaucrat, to a relationship-oriented leader or political bureaucrat.…”
Section: Explosion Of Interaction Needs and Emergence Of Instant Intesupporting
confidence: 58%
“…334-335) point out, the spaces for public leaders are created at the interface between boundaries of the public and the private, politics and administration, the citizen and delivery, and thus leadership is essentially about "communicating strategically". Siegel (2010) analyzed the role of the municipal chief administrative officer (CAO) in a context that shares many useful elements with our approach. The municipal civil servant, as many other managers, must lead in three directions (Mintzberg, 1997;Siegel, 2010).…”
Section: Local Leadership As Interaction In Governance Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Siegel () positions these dimensions and capabilities within a transformational leadership framework of ‘leading down’, ‘leading out’, and ‘leading up’. Leading down is ‘to integrate horizontally the diverse departments responsible for all of these activities into one corporate entity’ (Siegel : 146). Leading out is about engaging, negotiating, and facilitating positive outcomes on a range of issues with diverse internal and external actors and interests.…”
Section: The Role Of the Local Government Ceomentioning
confidence: 99%
“…David Siegel [12] has concluded that "leadership of a Chief Administrative Officer, have a great impact to the employees as well as to the image of the mayor and his council. A Chief Administrative Officer can make a mayor or council look good or bad.…”
Section: Introductionmentioning
confidence: 99%